Analysis of the Effect of Capital Structure, Dividend Policy, and Liquidity on Firm Value (Study on Building Construction Sub-Sector Companies Listed on the IDX in 2017-2019) Listed on the IDX in 2017-2019) - Yosepan Selly; Gendro Wiyono; Ratih Kusumawardhani (UNIVED Press, 2024)
This study aims to obtain empirical evidence of the effect of capital structure, dividend policy, and liquidity partially on firm value in building construction sub-sector companies listed on the IDX in 2015-2019. This type of research is descriptive quantitative. The population in this study were building construction sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2015-2019 period totaling 18 companies. While the sample in this study were some of the building construction sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2015-2019 period that met the research criteria. The sample selection was carried out using purposive sampling method, which is a sampling method tailored to certain criteria. The type of data used in this study is secondary data. The data source used in this study comes from the financial statements of building construction sub-sector companies on the idx.co.id website. The data analysis technique uses linear regression. Based on the results of data analysis, the following conclusions are obtained: (1) Partially, the capital structure variable has a positive and significant effect on firm value; (2) Partially, the dividend policy variable has a positive and significant effect on firm value; and (3) Partially, the liquidity variable has a positive and significant effect on firm value.